Assessment of the Pallet Unit Load Stability by Simulation Methods - Tomasz Matyja (Communications - Scientific letters of the University of Zilina, 2020)
The paper presents a simulation model of a loading unit dynamics, with a layered structure, wrapped with a stretch film. Stretch film wrapping is the most commonly used and cheap method of securing the load unit. The model, proposed by the author, allows assessing the stability of the unit during the transport operations, when the loading unit is subjected to inertial forces. Deformations of a unit and prediction of its disintegration in extreme cases can be evaluated based on results of a simulation. The value of the necessary containment force as well as the number of wraps with the pre-stretched film, can also be estimated. In effect, simulations can reduce the amount of film used and the number of stability tests performed experimentally.